PELATIHAN NASIONAL PENYUSUNAN MODUL P5 MENGGUNAKAN KREASI IDE MEDIA SERBANEKA PADA KEPALA SEKOLAH DAN GURU: Media Serbaneka, Modul P5, Kurikulum Merdeka - AHMAD HAQ (Universitas Negeri Surabaya, 2023)
The central government launched an independent learning curriculum which will be implemented starting in 2021. There are several school institutions trying to adapt the curriculum that is in force. Many academics, even practitioners socialize this either through seminars, training, coaching and so on. However, implementation does not necessarily go well, socialization activities related to this curriculum seem to be uneven. This causes problems for many schools. These problems include the lack of understanding and the low curiosity of the participants, that is, the trainees tend to be skeptical of the Independent Curriculum. This condition has an impact on the low understanding of educational implementers in designing modules according to the Independent Curriculum. Another problem is the adaptation of the media-based learning process used, so that the need for attention to teaching materials such as modules is very efficiently arranged in the creation of ideas that have been designed and forms effective and efficient media, while in fact there are still many participants who are constrained by this. The purpose of dissemination of coaching through this training is both by providing specific competencies in order to gain understanding and competence for participants, namely school principals and teachers in compiling modules according to the independent curriculum. So, the solution offered is to carry out a scientific design which is disseminated through training and mentoring for education implementing participants in the preparation of the P5 module (Project of Strengthening Pancasila Student Profiles) using various creative media ideas.